Plan estratégico para la empresa mi buen pollo del cantón Piñas provincia de el Oro - Torres Saritama, Noemí del Rocío (2017)
The elaboration of a "Strategic Plan for the company Mi Buen Pollo del Cantón Piñas, Provincia del Oro" was developed with the purpose of making an accurate review of the processes carried out by the company and reducing internal weaknesses, controlling the threats Which may affect the development of business activities. Among the methods and techniques used are: Scientist who served to consult the topics related to the research as they are, concepts, ideas of the strategic plan and other knowledge that serve to sustain the theoretical framework; Deductive was used this method to carry out a situational diagnosis of the company Mi Buen Pollo and give solutions to conflictive situations, undergoing a self-analysis that should lead to a concrete action plan that allows the identification of the rules, laws and regulations to do Applied; Inductive this method allows to know the results of the surveys applied to the clients, employees and interview to the Manager, therefore we will be useful for the elaboration of the SWOT Matrix, considering the economic, political, social and cultural factors that represent the influences of the scope External of the company, that affect its internal work; Analytical allowed to elaborate the Matrix of High Impact that allows to generate the strategic objectives with the purpose of obtaining a better yield in the commercialization of the products offered by the company; Statistical was used for tabulation of the surveys and thus give a statistical structure of graphs, where you can perceive the actual percentages of the information obtained to the population under study. The techniques applied were: direct observation, the interview conducted with the company manager and the surveys applied to the 26 employees and the 28 clients who with their answers allowed to detect the internal and external problems that the company faces, and to extract the strengths and weaknesses. First, an external analysis was carried out in the company, which allowed me to define the opportunities and threats of the company, whereby the EFE matrix was constructed, where the weighted total is 2.61, which indicates that the company is taking advantage of the Opportunities to minimize the impact of threats. Through the EFI matrix (evaluation of internal factors), we obtained a weighted value of 2.66 which allows us to determine that the company Mi Buen Pollo maintains a strong internal position, which guarantees that it can go ahead and develop in a positive way in the middle. With the internal and external analysis, the SWOT matrix was constructed, which allowed the delimitation of opportunities, threats, strengths and weaknesses. The high impact matrix was built and the FO, DO, FA, DA combination was obtained As a result of the strategic objectives. Regarding the results of the proposal of the Strategic Plan for the company "My Good Chicken", it is proposed: to carry out an Advertising Plan in local media (radio) in order to attract more customers and achieve greater market positioning, To have a highly professional and qualified staff that provides an excellent service with efficiency and effectiveness, give the company a corporate identity that satisfies the aspirations of all its stakeholders, Encourage the creation of a Human Resources department and lastly We have the implementation of a plan of promotions in the company My Good Chicken. Finally, it should be remembered that the effective formulation of the strategies does not guarantee the successful implementation of the strategies if there is no continuous monitoring and control, therefore, actions are established for evaluation. Finally, the respective conclusions and recommendations of the work that cover the most relevant aspects of the strategic planning applied to the company Mi Buen Pollo are presented.